Comparative analysis of SRM, BLDC and induction motor using ANSYS/Maxwell - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2021)
In modern industrial fields, the production of electrical machines has become more important than ever. Engineers and researchers mainly prefer machines that show the best performance with especially high torque, reduce losses and increase efficiency. In this study, we aimed to design, compare and choose the best design by employing the at the same power per volume, stacking factor stator, rotor material and input parameters matched as closely as possible, and then to evaluate their performance by using the ANSYS/Maxwell 2 D software. Mainly used three motors in the industry, such as switched reluctance motor (SRM), brushless direct current (BLDC) motor and induction motor (IM) were compared. Nowadays, these motors are popular and commonly used in the electric vehicles such as e-scooters, e-cars, e-bicycles and e-drones. Accordingly, this study would also be helpful for electric motors designers who prefer electric motors with high efficiency and torque. © 2021 IEEE.
Keywords: ANSYS/Maxwell 2D; BLDC; Efficiency; Induction motor; SRM; Torque